Psychosemantical Approach to Volition Research - Chalikova, O; Kiseleva, D (KnE Life Sciences, 2018)
The research into the ratio of objective and subjective indicators of the volitional qualities of an individual conducted by the Department of General and Social Psychology of the UrFU discovered some limitations of the corresponding approaches to such multidimensional objects as volition. The research into individual semantic fields of the concept of ‘volition’ will make up for the existing methodological gap in that area. The research was conducted in 2017. The sample consisted of 77 students of the Department of Psychology. The semantic differential method in the modification by I.L. Solomin was used as a basis. The list of objects has been changed and expanded according to the tasks of the research. The second method of research is the associative experiment. The results were processed by using the methods of cluster analysis, factor analysis and content analysis. An analysis of individual cluster trees discovered a rather large variability of the semantic relationships between the objects under study. Several sub-groups of respondents were identified according to the individual characteristics of the semantic fields in relation to the object ‘volition’, the sub-group ‘success of activities’, the sub-group ‘personality qualities’, the subgroup ‘negative objects’ and the sub-group ‘object is not defined’. Most students consider volition either as an applied tool of educational or professional activities, or as a self-sufficient personal mechanism. With the help of factor analysis, the features of the affective attitude toward the object ‘volition’ in respect to the sample as a whole are revealed. The associative experiment made it possible to identify the key topic markers that characterize the volition of respondents of different semantic sub-groups. For the sub-group ‘success of activities’, it is ‘power’; it is ‘time’ for the sub-group ‘personality qualities’, in particular, ‘responsibility’; it is ‘firmness’ for the sub-group ‘negative objects’. The psychosemantics approach in studying volition allows us to identify topics that clarify the semantic nuances of the concept of ‘volition’ in the minds of the subjects. The method of the semantic differential and the method of associative experiment are mutually complementary with respect to research into the semantic sphere of a personality. The results obtained provide a necessary part of a comprehensive study of volition and the volitional qualities of a person. Keywords: volition, volitional qualities, responsibility, students, psychosemantic approach, semantic differential, semantic field, associative experiment, semantic structures of consciousness, representations, individuality, cluster trees, topic markers